Genetic and genomic analyses for pig survival using threshold models - Leite, Natália Galoro (2019)
Pig survival is an economically important trait that has animal welfare implications. Although survival is highly affected by the environment, previous studies reported genetic variability of this trait, indicating the opportunity for improvement through selection. Survival is a binary trait, which is usually evaluated by linear models. However, non-linear models such as threshold models are more statistically suitable, since they consider the categorical nature of this trait. Besides trait phenotypes and pedigree, genomic information is currently included in the major commercial pig breeding programs. One of the genomic evaluation methods that permits the incorporation of such different source of information is the so called single-step genomic BLUP (ssGBLUP), which includes information from phenotypes, pedigree and genotypes in a single evaluation. In this context, we aimed to estimate (co)variance components for survival at farrowing, and during lactation, nursery and finishing phases using threshold models, and to compare the individual breeding value prediction accuracies obtained using traditional pedigree-based BLUP and ssGBLUP methods. Individual survival records for four different production stages were collected for a crossbred pig population, which was produced from 4,403 litters and raised at a research farm in the Netherlands. Two-trait additive-maternal threshold models, without the inclusion of genomic information, were used for (co)variance components estimation. After that, direct and maternal breeding values were estimated using BLUP and ssGBLUP methods, and individual prediction accuracies were obtained based on posterior standard deviation. Heritabilities for the four survival phases were low, ranging from 0.04 to 0.12. Farrowing and Lactation survival were affected by dam and piglet additive genes effects. The additive direct and maternal components were equally important at farrowing, whereas piglet’s own genetic merit was the most expressive during lactation. Nursery and finishing survival showed the same or higher heritabilities compared to pre-weaning stages. The genetic correlation between the pre-weaning phases was high (0.68), whereas between the post-weaning measurements was moderate (0.42). The incorporation of genomic information into survival evaluations, through ssGBLUP, increased the prediction accuracy, on average, from 5.6% to 16.4% for direct breeding values and from 23.1% to 29.5% for maternal breeding values compared to BLUP. Although the heritabilities for survival in the different evaluated productive stages were low, there is genetic variability to be explored, which can be accurately benefited by the inclusion of genomic information. Keywords: Mortality. Post-weaning. Pre-weaning.